(untitled) (Brazilian Journal of Health Research, 2025)
Introduction: Self-injurious behavior (SIB) in adolescents is globally recognized as a serious public health issue that requires ongoing attention due to its association with psychiatric disorders and a higher likelihood of future suicide. Identifying risk and protective factors is essential to halt the progression of this phenomenon and to develop more effective coping strategies. Moreover, understanding the various biopsychosocial aspects that influence the persistence of this form of self-inflicted violence is of great importance for its prevention and intervention. Objective: To describe some of the risk and protective factors influencing SIB, based on Bronfenbrenner’s bioecological theory, which considers the complex interactions among different environmental systems. Methods: A theoretical and reflective study grounded in dialogue with the works of various authors from the scientific literature. Results: The ecological perspective not only broadens the understanding of self-injury but also highlights the need for multifaceted interventions that address the multiple levels of adolescents’ social and cultural environments. Conclusion: This approach is crucial for promoting mental health and well-being among affected youth, emphasizing the importance of early and appropriate interventions.